Honokiol Alleviates Hypertrophic Scar by Targeting Transforming Growth Factor-β/Smad2/3 Signaling Pathway - Zhao, Danyang; Wang, Yu; Du, Chao; Shan, Shengzhou; Zhang, Yifan; Du, Zijing; Han, Dong (Frontiers in Pharmacology, 2017)
Hypertrophic scar (HPS) presents as excessive extracellular matrix (ECM) deposition and abnormal function of fibroblasts. However, there is no single satisfactory method to prevent HPS formation so far. Here we found that honokiol (HKL), a natural compound isolated from Magnolia tree, had an inhibitory effect on HPS both in vitro and in vivo. Firstly, HKL could dose-dependently down regulate the mRNA and protein levels of type I collagen (COL I), type III collagen (COL III) and α-smooth muscle actin (α-SMA) in hypertrophic scar-derived fibroblasts (HSFs). Secondly, HKL suppressed the proliferation, migration abilities of HSFs and inhibited HSFs activation to myofibroblasts, but had no effect on cell apoptosis. Besides, the in vivo rabbit ear scar model further affirmed the inhibitory effects of HKL on collagen deposition, proliferating cell nuclear antigen (PCNA) and α-SMA. Finally, western blot results showed that HKL reduced the phosphorylation status of Smad2/3, as well as affected the protein levels of matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinase1 (TIMP1). Taken together, this study demonstrated that HKL alleviated HPS by suppressing fibrosis-related molecules and inhibiting HSFs proliferation, migration as well as activation to myofibroblasts via Smad-dependent pathway. Therefore, HKL could be used as a potential agent for treating HPS and other fibrotic diseases.